2021
DOI: 10.3390/ani11113215
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Infection with Porcine Circovirus Types 2 and 3 in the Wild Boar Population in the Campania Region (Southern Italy)

Abstract: In recent years, porcine circovirus (PCV) infection has been documented as an important and emerging health concern for livestock and wildlife worldwide. The purpose of the present study was to assess the molecular prevalence of PCV-2 and PCV-3 and to clarify the epidemiological role of wild boars in the circulation of this virus in Campania, Southern Italy. For this purpose, samples from several organs were collected during the hunting season 2017–2018 from 148 wild boars in the Campania region. Quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…On the other hand, PCV-3 infection in the second-third of gestation, due to the lack of fetal immunocompetence, may lead to the birth of immunotolerant pigs. This latter scenario would explain potential persistent PCV-3 infections postnatally, as it has also been sporadically observed in the abovementioned work, in which few animals were PCR positive at all sampling points during their lifespan [19]. However, the current available laboratory techniques do not allow the full assessment of such condition.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…On the other hand, PCV-3 infection in the second-third of gestation, due to the lack of fetal immunocompetence, may lead to the birth of immunotolerant pigs. This latter scenario would explain potential persistent PCV-3 infections postnatally, as it has also been sporadically observed in the abovementioned work, in which few animals were PCR positive at all sampling points during their lifespan [19]. However, the current available laboratory techniques do not allow the full assessment of such condition.…”
Section: Discussionmentioning
confidence: 79%
“…These latter cases would be diagnosed under the scope of the recently proposed PCV-3-RD [7,15]. Moreover, this virus has also been detected in high prevalence in wild boars [17][18][19] and, sporadically, in other wildlife species [20], highlighting the importance of wildlife surveillance to look for potential reservoirs of infectious pathogens or spillover events [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed PCV2 sequences from wild boar and domestic pigs were closely related in Slovenia [ 49 ] and Germany [ 46 ], as well as in Hungary and Romania [ 45 , 47 ]. In Poland, nine PCV2 genotype b sequences from wild boar showed very high identity with sequences from domestic pigs, a pattern also noted among genotype a [ 48 , 50 ].…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies showed PCV2 sequences from wild boar and domestic pigs were closely related in Slovenia [49], Germany [46], and Hungary and Romania [45,47]. In Poland, nine PCV2 subtype b sequences from wild boar showed very high identity with sequences from domestic pigs, a pattern also noted among subtype a [48,50].…”
Section: Transmission and Epidemiologymentioning
confidence: 95%